(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: In this work, the optical properties for thin film of Coumarin 334 organic laser dye doped with PVA polymer and AL2O3 nanoparticles are determined at different concentrations, dissolved in ethanol solvent. Methods: Solutions at concentration (10-4 M) from coumarin (334) dye in ethanol solvent at Different concentrations from dye (1, 3, 5, and 7) ×10-5 M were prepared. Results: The AFM measurements show that the grain size, root mean square and roughness belong to the surface of the thin films rises with thickness rise for thin films . It has also increased the absorbance due to the increase in concentration. Conclusion: By using Gaussian beam from CW pulsed laser at 457 nm, we used Z-scan to study the nonlinear optical properties. The nonlinearity of thin film highly excels the pure dye solutions.